The ethics of life beyond bio-centered humanism of Hans Jonas - Pommier, Eric (Universidad Pedagógica y Tecnológica de Colombia, 2020)
I will argue, first, that both the charges of anthropocentrism and anti-humanism made against the philosophy of Hans Jonas have no legitimacy. They represent an abstract vision of human existence. Therefore, I will indicate, in a second moment, that Hans Jonas founds his ethics on a biocentric ontology of life in order to highlight the superior value of humanity and to show that this value is compatible with a discourse of respect for life and nature. However, I will emphasize, thirdly, the real difficulties that Jonas encounters. Indeed, in the first place, he does not think about the relationship between living beings and, therefore, he fails to develop an environmental ethic. Second, he does not fully articulate his formal ethics with his medical ethics. That is the reason why I wish to indicate how it is possible to overcome these limits in order to open the way to an ethics of life that is truly compatible with humanism.